Collective action for small-scale producers of agricultural biodiversity products - Kruijssen, Froukje; Keizer, Menno; Giuliani, Alessandra (International Food Policy Research Institute, 2007)
The role of well-functioning markets for development is now widely recognized, however the challenge remains to make these markets benefit the poor and the environment. Increasing attention is being given to the potential role markets can play for agrobiodiversity conservation through product diversification and increasing competitiveness in niche and novelty markets. Bioversity International has undertaken several studies that explore the use of market-based approaches to on-farm agrobiodiversity management and livelihood improvement. Case studies have been developed on a range of species, varieties and derived products, including underutilized species and commodities in several regions of the world. This paper explores how the theory of collective action can provide a more synthetic understanding of how market chains operate and how changes in the market chain and market institutions can permit a more equitable distribution of welfare benefits. The case studies illustrate the need for improved trust, a mutual understanding of each actor’s involvement and the need for an agreed process of collective action that involves a high level of community participation to achieve an improved market chain organization benefiting the poor. The cases differ in their degree of collective action, the level of market organization and the ways in which handling, processing, and innovative marketing add value to the agrobiodiversity products. Comparative analysis of these cases identified a range of options and situations in which market development can support agrobiodiversity conservation and livelihoods. Bringing together these experiences will also help to identify the situations in which a collective approach can maximize the capturing of market benefits for smallholders. Trade-offs between income generation, livelihood security, and agrobiodiversity conservation should be further examined in order to find solutions that support sustainable development of poor communities that manage agricultural biodiversity.